THE INFLUENCE OF VIDEO MARKETING CONTENT STRATEGY ON YOUTUBE ON CONSUMER LAYALTY TO FASHION BRANDS - Dony Martias (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The development of digital technology has changed the way fashion brands interact with their consumers, one of which is through video marketing on YouTube. Video marketing content strategy not only functions as a promotional tool, but also as a medium for building brand awareness, increasing engagement, and strengthening consumer loyalty. This research aims to analyze the influence of video marketing content strategies on YouTube on consumer loyalty to fashion brands through a literature review approach. This research uses a descriptive- analytical method by collecting and analyzing various academic sources, such as scientific journals, books, industry reports, and digital marketing articles. The study results show that factors such as strong storytelling, high visual quality, interactive engagement with the audience, and consistency in content presentation have a significant impact on customer loyalty. Additionally, collaboration with influencers and leveraging analytics to measure content effectiveness also contributes to improving long-term relationships between brands and consumers. The implications of this research indicate that fashion brands need to optimize their video content strategy by considering these factors in order to maintain and increase customer loyalty. With the increasing consumption of digital content, video marketing on YouTube has become an effective and relevant strategy in building emotional connections with consumers and strengthening brand positions in the competitive fashion industry.